2015
DOI: 10.25110/arqsaude.v18i2.2014.5169
|View full text |Cite
|
Sign up to set email alerts
|

Dramatização Como Instrumento De Informação a Respeito Do Tabagismo Entre Escolares

Abstract: CAMÊLO, C. P. R.; LIMA, L. A.; SARDINHA, M. C.; RABAHI, M. F. Dramatização como instrumento de informação a respeito do tabagismo entre escolares. Arq. Cienc. Saúde UNIPAR, Umuarama, v. 18, n. 2, p, 69-73, maio/ago. 2014. RESUMO:O tabaco é a segunda droga mais utilizada entre adolescentes e seu uso contínuo causa cerca de 200.000 mortes por ano no Brasil, dessa forma, é relevante investigar com frequência a extensão do tabagismo e o conhecimento dessa população sobre o tema, para assim orientar estratégias pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Literature publications on the subject corroborate this assertion, showing that young people from public schools are more easily related to tobacco experimentation 43,52,53 . The Malta et al 54 study detected a higher risk of tobacco use among public school students, whose work showed also that not having friends favors tobacco use.…”
Section: Discussionmentioning
confidence: 90%
“…Literature publications on the subject corroborate this assertion, showing that young people from public schools are more easily related to tobacco experimentation 43,52,53 . The Malta et al 54 study detected a higher risk of tobacco use among public school students, whose work showed also that not having friends favors tobacco use.…”
Section: Discussionmentioning
confidence: 90%